Model and strategies for the development of coffee in Jambi Province to respond the global market demand - Rosmeli Rosmeli (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2019)
Indonesia is one of the world’s top coffee producing countries after Brazil, Vietnam, and Colombia. Although not as the largest coffee producers, Jambi Province has three types of coffee as the region’s mainstay product, namely Robusta coffee, Arabica coffee, and Libtukom (Liberika Tungkal Komposit) coffee. The demand for these three types of coffee is quite high. However, there are various problems faced including low land productivity, crop failure, and distribution channels that are not profitable for farmers. Based on this, the study aims to formulate a model and strategies for developing Jambi Province’s coffee. Main data used were derived from coffee farmers, experts and stakeholders, and related agencies. Data were analyzed using SWOT and QSPM analysis. It was found that there are eight priority strategies for developing Jambi Province’s coffee, namely 1) cutting off distribution channels, 2) working directly with relevant agencies, 3) increasing promotion of Jambi’s coffee, 4) coffee as one of the Jambi Province icons, 5) coffee product innovations, 6) cooperation with export destinations, 7) improving knowledge and processing technology, and 8) improving human resources.